Espresso Book Machine (EBM) and Libraries - Emre Çetin (Türk Kütüphaneciliği)
This article, which is in the form of a short opinion paper, gives introductory information about Espresso Book Machines (EBM) that convert digital content into books in five minutes and concludes with the idea that EBMs have enabled the utilisation of new methods in improving library collections.